A probabilistic pedotransfer function for estimating the soil water characteristic curve and quantifying its uncertainty - Xin-Yuan Wang; He-Fu Pu; Ming Min; Yu Miao; Sen-Lin Xie; Xiao He (Computers and Geotechnics, 2027)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Metagenomic indications of potential pathogen-associated and antibiotic resistance risks following UV–chlorine disinfection in sprout production - Yufei Wei; Lin Zhu; Xiangfu Jin; Huangli Yao; Shanshan He; Pu Feng; Feihong Yu; Yulu Xiang; Zhiheng Li; Shanying He (Environmental Pollution, 2026)

Visibly transparent photoluminescent film for energy-efficient chromatic glazing - Yingxiao Li; Quan Gong; Jihong Pu; Lin Lu (Chemical Engineering Journal, 2026)

One-step construction of quaternary phosphonium-based hypercrosslinked polymers for efficient and rapid removal of phenolic pollutants - Lin Yao; Pu Xiong; Hao Chen; Li Zhang; Meng Wang; Yafen Dai; Yigang Ding (Journal of Environmental Chemical Engineering, 2026)

Mechanism of surface-functionalized materials for efficient iodide removal: Performance and theoretical insights - Meng Ren; Xuedan Cui; Sai Yuan; Ying Yang; Xiaotian Xu; Pengjie Zhao; Tianda Pu; Guilan Duan; Yinjie Zhang; Aijun Lin (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Molecular dynamics-guided titanium platform with chitosan-assisted bacterial anchoring for sequential antibacterial and osteogenic functions - Jiaying Li; Junkai Hu; Jiamin Li; Weihan Zheng; Jiejie Wang; Tao Lin; Jiahao Pu; Tingting Chen; Mingrui Li; Hang Sang; Jianlin Shen; Lincong Luo; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Versatile poly (deep eutectic solvents) electroactive chitosan eutectogel for infected wound healing and monitoring administration” [Carbohydrate Polymers 352 (2025) 123192] - Shuai Liu; Jiamian Zhan; Zhenyu Liu; Xiaoying Tan; Jianxing Huang; Chunyi Pu; Rurong Lin; Yu Chen; Qi Luo; Xiaozhong Qiu; Honghao Hou (Carbohydrate Polymers, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Significant crust-thinning beneath the Ilan Plain of Taiwan for revealing westward impingement of the Okinawa Trough opening into Taiwan Orogeny - Ya-Chuan Lai; Cheng-Horng Lin; Min-Hung Shih; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Tectonophysics, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Uncovering an aseismic slab for showing the flipping of subduction polarity in the Taiwan area - Lin Cheng-Horng; Min-Hung Shih; Ya-Chuan Lai; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Journal of Asian Earth Sciences, 2026)

Coupled thermo-hydro-mechanical analysis of multistage evolution in matrix failure and fracture deformation across varying influencing factors for an enhanced geothermal system - Xingjie Lin; Zhihong Lei; Yikun Liu; Silin Pu; Lihang Zhang; Sixiang Ling; Rui Deng (Geomechanics for Energy and the Environment, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Synthetic microbial community shields wheat from cadmium: Coordinating host metabolic reprogramming and rhizosphere microenvironment regulation - Huangxin Chen; Lin Kong; Yaoyuan Zhang; Guiyin Wang; Xin Qi; Changlian Xu; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Journal of Hazardous Materials, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

Design, preparation and performance study of DAP-1 based conductive energetic composite - Wan-Jun Wei; Rui Pu; Yu-Ruizhi Lin; Ying-Qi Mao; Qi-Long Yan; Shao-Li Chen (Chemical Engineering Journal, 2026)

Subduction-controlled Late Triassic rifting along the northern margin of Gondwana - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Yang Wang; Jun-Pu Lv; Xin-Yu Hou (International Geology Review, 2026)

Hierarchical Studies in TRAP2 Mice Demonstrate that Neuronal Activation and Mitochondrial Networks Integration Constitute the Key Mechanism Underlying Painful Syncope - Xueyin Pu; Yulu Xia; Ziwei Ni; Changlei Zhu; Kunlong Zhang; Bozhi Liu; Rui Lin; Jingxuan Zhu; Hui Liu; Shujiao Li; Yunqiang Huang; Feifei Wu; et al. (Neuroscience Bulletin, 2026)

Interfacial confinement effects in MOF-derived C/CuO for peroxymonosulfate activation: Non-radical pathway-mediated thiamethoxam degradation - Shibo Zhu; Mengjie Pu; Chao Zhang; Zihan Shen; Mi Lin; Xinzhi Wang; Zhe Zhang; Bentuo Xu; Mingzhi Huang (Journal of Environmental Management, 2026)

Shifting carbon emission dominance across subway lifecycle phases: A refined subsystem-interaction assessment - Jing Pu; Chen Cai; Shijun Chen; Ru Guo; Ruimin Lin; Xingyu Ding; Jia Liu; Kaiming Peng; Xiangfeng Huang (Environmental Impact Assessment Review, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

Deciphering the spatial patterns of a springtime microbial community: Structure, function, and key drivers in the Southern Yellow Sea - Yang Yuan; Wei He; Long Jiang; Lin-Qiong Wang; Xian-Pu Ji; Dao-Feng Zhang; Wen-Jun Li (Journal of Environmental Sciences, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Corrigendum to “Recombinant IL-21 alleviates bacterial enteritis in grass carp by enhancing the intestinal barrier and suppressing the inflammatory response” [Fish Shellfish Immunol. 173 (2026) 111272] - Gaoliang Yuan; Xin Lin; Liying Qin; Xu Pu; Dexiang Feng; Yanwei Zhang (Fish & Shellfish Immunology, 2026)

Recombinant IL-21 alleviates bacterial enteritis in grass carp by enhancing the intestinal barrier and suppressing the inflammatory response - Gaoliang Yuan; Xin Lin; Liying Qin; Xu Pu; Dexiang Feng; Yanwei Zhang (Fish & Shellfish Immunology, 2026)

Scenario-driven dynamic Bayesian networks for adaptive emergency decision support in ship oil spill accidents - Fan Zhang; Xinrong Pu; Xi Huang; Lei Du; He Lin (Ocean Engineering, 2026)

3D-printed porous titanium alloy scaffolds modified with composite hydrogel-loaded emodin liposomes for the treatment of periprosthetic joint infection - Jiamin Li; Jiaying Li; Junkai Hu; Tingting Chen; Tao Lin; Jiahao Pu; Lincong Luo; Wenhua Huang (Chemical Engineering Journal, 2026)

The effects of ectomycorrhizal fungi inoculation on alleviating Cd stress in Pinus massoniana seedlings - Qian-Cai Lin; Ming Xu; Shan Wei; Qiu-Pu Yang; Jian Zhang (World Journal of Microbiology and Biotechnology, 2026)

Mooring lines structural health monitoring based on floating wind turbine response using an integrated ESAX-ResNet-50 model - Pu Xu; Zhipeng Lin; Ullah Zahid; Jixiang Zheng; Qiming Song; Bo Han (Ocean Engineering, 2026)

Waste lignin-based N/O-rich carbon nanofibers as bifunctional materials for efficient CO2 conversion and energy storage - Wei Hui; Xin Wang; Zao-Lin Hu; Ming-Yu Zhao; Jia-Xin Feng; Wen Chen; Xiao-Yu Xiao; Chuang-Qi Zheng; Lei Pu (Journal of Environmental Chemical Engineering, 2026)

Effect of 6-Month High-Impact and Resistance Exercise on Regional Strength and BMD of Spine: A Clinical Trial Combined with a Finite-Element Study - Pu Duan; Yinxia Nie; Shizhong Liu; Xiaoyu Xia; Rui Xu; Simin Li; Vadim V. Silberschmidt; Lin Meng; Juan Du; Dong Ming (Annals of Biomedical Engineering, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

How does recreation involvement in urban parks promote restorative effects? - Erkang Fu; Lin Li; Jiawen Zhou; Li Deng; Mingxuan Pu; Peilin Qu; Yijun Xu; Xi Li (Urban Forestry & Urban Greening, 2026)

Effects of in-situ stress direction and orientation of structure planes on rockburst generation in deep tunnels: 56 case studies - Ben-Guo He; Xiang-Rui Meng; Bo Lin; Hong-Pu Li (Tunnelling and Underground Space Technology, 2026)

A high-accuracy stacking model for automatic identification of aeolian saltating tracks in high-speed pictures - Mengjie Pu; Fanmin Mei; Chuan Lin; Mingjun Sui; Hongda Chen; Shenyang He; Weikai Wang; Chang Zhou; Jin Su; Jinguang Chen (Aeolian Research, 2026)

Structurally integrated lignin-derived biochar/CuFeO2 aerogel for salt-resistant solar-driven interfacial evaporation and wastewater purification - Yaopeng Pu; Na Jin; Yuyu Wang; Yulong Ma; Feng Lin; Yonggang Sun (Journal of Environmental Chemical Engineering, 2026)

Agglomeration of coal gangue particles in an ultra-supercritical CFB boiler: microstructure, thermodynamic modeling, mechanisms and prevention methods - Xiuting Yang; Junjie Li; Seokgi Ahn; Yongkang Han; Lin Pu; Chung-Hwan Jeon; Hua Wang; Xing Zhu; Tao Zhu; Dongfang Li (Fuel, 2026)

Injectable anti-inflammatory nanofiber hydrogel reprograms immunosuppressive tumor microenvironment via cascade-amplified immunogenic cell death - Ruo-Yun Zhang; Wei Yue; Yang Xuan; Long Qi; Lin-Lin Guo; Zhen-Zhen Zhu; Ming Yang; Zhang-Jie Pu; Guo-Qiang Li; Xin-Yi Mao; Ding Zhou; Zhao-Wei Zhang (Chemical Engineering Journal, 2026)

Natural variation in VrERF088 modulates drought tolerance during mungbean germination - Xi Zhang; Jinyang Liu; Shicong Li; Yun Lin; Yixiang Pu; Qiang Yan; Jingbin Chen; Ranran Wu; Na Yuan; Prakit Somta; Lixia Wang; Xin Chen; et al. (Theoretical and Applied Genetics, 2026)

The variability of phosphorus fractions and transport driven by rainfall at both plot and catchment scales - Zhixiang Sun; Lei Chen; Yu Pu; Yongqiang Lin; Qingqing Zuo; Jiayu Jiang; Tengyu Zhang; Kun An; Zhenyao Shen (Journal of Hydrology, 2026)

Expanded species diversity of fungi in metalliferous mine tailings ponds and their potential ecological roles revealed by PacBio sequencing - Yanying Li; Ting Huang; Weihang Zeng; Rongzhou Jin; Ye Wu; Zhipeng Chen; Qijie Cheng; Xinlin Yu; Xiao-lin Luo; Guan-xiong Wu; Jia-wei Li; Pu Jia; et al. (Journal of Hazardous Materials, 2026)

Comparisons of machine learning models for landslide susceptibility mapping in the Jiuzhaigou earthquake-affected area, China - Zuhao Lin; Sixiang Ling; Fei Luo; Fengxing Gao; Yanbing Pu; Minxuan Li; Xiaoyang Liu; Xiaoning Li; Chunwei Sun; Xiyong Wu (Bulletin of Engineering Geology and the Environment, 2026)

Blocking T-type calcium channels disrupts spermatogenesis in vivo and adversely affects spermatocytes in vitro by impairing mitochondrial function and autophagic flux - Xiuling Zhao; Lei Wang; Shiqin Huang; Lin Liu; Xiaorong Wang; Liping Pu; Hao Chen; Junyu Nie (Reproductive Toxicology, 2025)

Enhancing heavy metal immobilization in cropping systems via modified clay minerals: A machine learning- assisted meta-analysis - Wenwen Zhang; Pengjie Zhao; Tianda Pu; Wanjia Bao; Hantong Qie; Xiao Tan; Meng Ren; Aijun Lin (Journal of Environmental Chemical Engineering, 2025)

High-yield hydrogen from fluidized-bed biomass gasification via waste-derived anti-sintering composite sorbents - Baokun Li; Liangliang An; Shaoxiang Pu; Aoyang Zhang; Lin Li; Lunbo Duan; Ryang-Gyoon Kim; Xing Zhu; Hua Wang; Dongfang Li (Chemical Engineering Journal, 2025)

Dynamic structural reconstruction of CuO under reaction conditions enhances photocatalytic activity in C H bond functionalization - Shaohui Zhang; Jia Liu; Yan Pu; Yifang Zhang; Yingcong Wei; Huaxiang Lin; Jinlin Long; Rongjian Sa; Xianzhi Fu; Rusheng Yuan (Chemical Engineering Journal, 2025)

Corrigendum to “boosting sustainable monocyclic aromatics yield from catalytic fast pyrolysis of cotton stalk via a novel ZnZrOx-ZSM-5 tandem catalysis” [Chem. Eng. J. Volume 524, 15 November 2025, 168988] - Lingxi Bai; Haonan Li; Xingxiang Wang; Xin Pu; Zhipeng Lin; Shuzhen Zhou; Jiangbing Li; Xiaogang Wang; Jie Li; Lingtao Kong; Lanli Bai; Jichang Liu (Chemical Engineering Journal, 2025)

Microalgae-based removal of pharmaceutically active compounds (PhACs) from wastewater: Mechanisms and applications - Ye Lin; Xue Pu; Jingyuan Xia; Xiyang Lu; Heyang Hu; Jiawei Bai; Fuyuan Guo; Shijian Ge; Shuang Qiu (Algal Research, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

Numerical acceleration method for static and dynamic analysis of deepwater laying pipelines - Pu Xu; Jixiang Zheng; Weiwei Lin; Yiming Hu; Naiquan Ye (Ocean Engineering, 2025)

Design, characterization, and application of novel antimicrobial peptides against Bacillus cereus - Xiaowei Chen; Yi Cai; Shanyu Huang; Donglin Pu; Zhenbo Xu; Thanapop Soteyome; Jun Zhu; Yanrui Ye; Xiaomei Lin (International Journal of Food Microbiology, 2025)

Combined non-volatile and volatile metabolite profiles and antioxidant activities reveal the enhancement of traditional “steaming and Sun-drying nine times” on the functional properties of jujube - Yu Liu; Lijuan Zhang; Haijiao Lin; Zengyi Song; Pu Xu; Liming Zhang; Binbin Wei (Food Chemistry, 2025)

Fe-Mo bimetal-modified catalytic ceramic membrane enabling Fenton reaction for highly efficient removal of micropollutants from water - Pei Wang; Pu Li; Chencheng Dong; Chao Yang; Lin Lin; Xiao-yan Li (Desalination, 2025)

Boosting sustainable monocyclic aromatics yield from catalytic fast pyrolysis of cotton stalk via a novel ZnZrOx-ZSM-5 tandem catalysis - Lingxi Bai; Haonan Li; Xingxiang Wang; Xin Pu; Zhipeng Lin; Shuzhen Zhou; Jiangbing Li; Xiaogang Wang; Jie Li; Lingtao Kong; Lanli Bai; Jichang Liu (Chemical Engineering Journal, 2025)

Biodiversity Buffers Phytoplankton Biomass Production Against Nanoparticle Pollution Through Increased Facilitation - Yiping Zuo; Qianna Xu; Michael Southard; Guangxing Zhang; Lan Gan; Hao Zhang; Pu Yan; Louis Walls; Mary Steinbeck; Muhan Zhao; Yongsheng Chen; Lin Jiang (Ecology Letters, 2025)
Although biodiversity is widely recognised for its role in maintaining ecosystem functioning under environmental change, its importance has received relatively little attention in the context of emerging environmental stressors such as nanoparticles. By assembling phytoplankton communities across a gradient of species richness and exposing them to varying concentrations of copper oxide nanoparticles, we experimentally explored how biodiversity modulates ecosystem functioning under nanoparticle exposure. We found that the positive effect of biodiversity on phytoplankton biomass production was amplified at higher nanoparticle concentrations, allowing diverse communities to maintain biomass despite strong inhibitory effects of nanoparticles on monocultures. This enhanced biodiversity effect was primarily driven by increased complementarity, specifically through more frequent facilitative interactions among species under nanoparticle stress. Our findings advance the understanding of how biodiversity preserves ecosystem functioning and underscore its role in mitigating the impacts of emerging anthropogenic stressors.

Investigating morphological effects of estuarine channel branching on saline water intrusion: a case study of Modaomen Estuary - Pu Wang; Liang Hong; Juli Lin; Hongyue Liang; Haiwei Li; Chao Tan; Hui Chen; Feng Liu (Frontiers in Marine Science, 2025)
Within the context of global change, morphological evolution in estuary regions and the related effects on water resource safety are key concerns for the sustainable management of river deltas. Channel branching controls the morphological evolution patterns and sedimentary regime in river deltas and generally occurs in response to natural conditions and human activities. In this study, we focused on the impacts of channel branching on saline water intrusion in the Modaomen Estuary in China. The riverine discharge through the Modaomen Estuary supplies freshwater source for the Guangdong- Hong Kong- Macao Greater Bay Area; and morphological evolution greatly affects saline water intrusion in this region, posing a threat to freshwater security. In this study, we constructed an idealized model with a prototype of Modaomen Estuary while considering single and double channels, to explore the impacts of channel branching on saline water intrusion in estuaries. The results indicated that channel branching greatly influenced the morphological structure of the mouth bar in the estuary. The magnitude of saline water intrusion occurred more significantly during the neap tide than spring tide in both the single- and double-channel simulations. Channel branching exhibited different effects on the saline water intrusion during the spring and neap tides, by affecting the estuarine dynamics and circulation. Furthermore, the mouth bar exerted a ‘blocking effect’ on the intrusion and recession of saline water. Overall, our study presents scientific guidelines for estuarine regulation projects to ensure water resource safety and promote effective estuarine management.

Assessment of true laterites for their use as liners in karst-depression tailings impoundments - Hai-Yan Gao; Jia-Ming Zhang; Ji-Pu Chen; Lin Tian; Kun Wang; Ze-Min Xu (Bulletin of Engineering Geology and the Environment, 2025)

Biocontrol mechanism of a newly isolated Streptomyces sp. JL2001 against Ralstonia solanacearum via aerugine - Zixian Zeng; Wei Cao; Hong Pu; Dousheng Wu; Sai Jiang; Meng Su; Yajing Wang; Zhi Wang; Xin Zhao; Juan Li; Shunxiang Li; Lin Jiang (Pesticide Biochemistry and Physiology, 2025)

CoFe-enhanced N-doped carbon nanotubes for activating peroxymonosulfate to remove carbamazepine under high-salinity conditions - Xiangxing Liang; Zhiyuan He; Jingxi Lin; Chuan Pu; Daixi Zhou; Fei Duan; Gang Lu; Mingshan Zhu (Journal of Water Process Engineering, 2025)

The advantages in crop yields and carbon footprints of maize-soybean relay strip intercropping - Zhidan Fu; Ping Chen; Ping Lin; Yiling Li; Kai Luo; Chao Gao; Tian Pu; Yuze Li; Yushan Wu; Xiaochun Wang; Taiwen Yong; Wenyu Yang (Journal of Environmental Management, 2025)

Atomically dispersed noble metal-Ox sites for electrocatalytic chlorine evolution - Chen Chen; Baoyi Guo; Tingting Liu; Ruting Lin; Yuyu Liu; Qiufeng Huang; Xiaofeng Zhang; Jiabao Huang; Fangren Qian; Shengyun Huang; Qingjun Chen; Xueqin Mu; et al. (Chemical Engineering Journal, 2025)

Exploring the direct influence of growth hormone on adamantinomatous craniopharyngioma cells - Zhiwei Xiong; Kai Li; Milai Yu; Zijing Wang; Yihan Wang; Rongjun Chen; Weizhao Li; Keying Zhang; Yucong Lin; Zhixuan Zhang; Haochuan Meng; Guowu Pu; et al. (Tissue and Cell, 2025)

Occurrence, trophic transfer and risk assessment of microplastics in fishery organisms from the Bohai Sea, China - Qilong Li; Lin Zhu; Xiaoying Pu; Qi Sui; Xuemei Sun; Xinguo Zhao; Rongyuan Wang; Bin Xia (Journal of Hazardous Materials, 2025)

Ionotropic receptors participate in the perception of sinigrin in Plutella xylostella adults - Zhi-Qiang Wei; Ya-Xin Wang; Ji-Xiang Wang; Xuan-Pu Luan; Chen Ding; Fan-Zheng Meng; Yu He; Qi Yan; Jin Zhang; Shuang-Lin Dong (Insect Biochemistry and Molecular Biology, 2025)

Evidence-based investigation of the efficacy and safety of venetoclax-containing regimens versus chemoimmunotherapy in chronic lymphocytic leukemia - Pu Yao; Jiao Zhang; Xiaowen Wang; Changsheng Jia; Lin Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The Evolution of the Order Siphonaptera Inferred from the First Mitogenome of the Family Pygiopsyllidae - Xiaoxia Lin; Ju Pu; Wenge Dong (Acta Parasitologica, 2025)

Steroidal saponins and homoisoflavonoids from the fibrous roots of ophiopogon japonicus and their anti-pulmonary fibrosis activities - Hang-Yi Pu; Yu Cao; Xi-Lang Jiang; Lin-Han Yang; Ming-Kui Wang; Fei Wang; Lun Wang (Natural Product Research, 2025)

Rhodobacter sphaeroides reduces Pb accumulation by reshaping the intestinal microenvironment and improving liver oxidant resistance in common carp (Cyprinus carpio L.) - Qian Zhou; Yi Pu; Hongmei Deng; Jiayi Gong; Lin Guo; Jiayi Ma; Lisha Liu; Shu Yuan; Yanger Chen; Yanqiu Su (Journal of Hazardous Materials, 2025)

Regulation of electrode surface microenvironment by porous ion transport layer for High-Efficiency CO2 electrochemical reduction to ethylene - Hao-Yan Shi; Yan-Xin Chen; Yi-Hu Pu; Hai-Long Wang; Yi-Zhan Xie; Xin-Zhi Tian; Yang Yang; Ao-Sheng She; Wen Chen; Wei-Hua Yang; Xiu-Mei Lin; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Bionic striated muscle tissue microstructures synchronous promote in vivo electromechanical coupling and muscle repair - Qixiang Duan; Chunyi Pu; Zhenyu Liu; Si Shen; Shuai Liu; Rurong Lin; Jie Zhang; Yongqin Wang; Yunsong Liang; Weihong Jiang; Rongze Jiang; Jingyu Guan; et al. (Chemical Engineering Journal, 2025)

Uplift, tilting, and underlying structures of coastal northwestern Luzon, Philippines, deduced from marine terraces - Yiran Wang; Aron J. Meltzner; Jennifer Quye-Sawyer; Huili Yang; Yichen Pu; Jintang Qin; Lin Thu Aung; Zihan Aw; Andrea Denise A. Pamintuan; Noelynna T. Ramos (Quaternary Science Reviews, 2025)

Odorant receptor 75 is essential for attractive response to plant volatile p-anisaldehyde in Western flower thrips - Xuan-Pu Luan; Xiao-Tong Zhang; Zhi-Qiang Wei; Jin-Meng Guo; George F.O. Obiero; Merid N. Getahun; Qi Yan; Jin Zhang; Shuang-Lin Dong (Pesticide Biochemistry and Physiology, 2025)

Differential magmatism and tectonic evolution during the rift stage within the Baiyun Sag of the Pearl River Mouth Basin in the northern South China Sea - Bo Yan; Xuan-Long Shan; Zhe Wei; Guo-Li Hao; Peng-Lin Zhang; Ling Ma; Zhi-Hao Wang; Pu-Jun Wang; N.G. Boriskina (Gondwana Research, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Identification of Chlortetracycline Hydrochloride as a Antibacterial Compound Against Pseudomonas syringae pv. tomato DC3000 Through Natural Products Library Screening - Lin Jiang; Linghe Huang; Yajing Wang; Jing Li; Zixian Zeng; Wenlong Yang; Sai Jiang; Dousheng Wu; Zhi Wang; Shunxiang Li; Yanxia Huang; Hong Pu (Current Microbiology, 2025)

Multi-nanozyme cascade system for boosting colorimetric sensing by selective etching bimetallic MOFs - Yuhang Lin; Tianshuo Wang; Yuanhao Liu; Lianxi Pu; Mingxuan Jia; Xilong Zhou; Lijun Ding; Weiran Zhu; Kun Wang (Analytica Chimica Acta, 2025)

Discovery of phenoxazine congeners as novel α-glucosidase inhibitors and identification of their biosynthetic gene cluster from Streptomyces sp. CB00316 - Lin Jiang; Pingzhi Huang; Aijie Li; Bin Fen; Yani Zhong; Caijun Tang; Guangling Wu; Wenlei Wang; Yuhan Chen; Jian Pan; Genyun Tang; Hong Pu (Archives of Microbiology, 2025)

Functional characterization of chemosensory proteins in three sympatric Tomicus bark beetles feeding on Pinus yunnanensis: Implication for the conservation and divergence of ligand-binding profiles - Lin-Mei Pu; Peng-Fei Wang; Yu-Yue Lu; An-Jin Yang; Li-Li Liu; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

“Three-birds, one-stone” biomimetic nanozyme system based on oxygen vacancy structure-regulated cascade reaction for inflammatory bowel disease - Tianliang Li; Zhaoming Wang; Zhijie Wang; Yihuan Pu; Lixing Lin; Zeyu Li; Lifei Chen; Xinting Liu; Bin Cao; Yingying Chen; Zhenzhen Li; Zixuan He; et al. (Chemical Engineering Journal, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Investigation on coupling of reaction and separation in single catalytic packing packet - Xiaonan Liu; Zheng Lin; Guanyu Pu; Yong Sha (Chemical Engineering Journal, 2025)

Multifunctional LaCrO3-Gd0.1Ce0.9O1.95 fuel electrode with dual-phase in-situ exsolution for solid oxide cells - Shiming Hu; Shuidan Gu; Liangyou Lin; Lu Zou; Jian Pu; Bo Chi (Chemical Engineering Journal, 2025)

The effect of interfering ions on the degradation of organic pollutants by two types of activated persulfates over Fe-based catalysts in water: A meta-analysis - Pengjie Zhao; Hantong Qie; Xuedan Cui; Wenwen Zhang; Tianda Pu; Wanjia Bao; Xiaolu Li; Aijun Lin; Meng Ren (Chemical Engineering Journal, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

The effect of powdery mildew on the cell structure and cell wall composition of red clover - Zhiling Lin; Xiaojian Pu; Wenhua Du (European Journal of Plant Pathology, 2025)

Plant Acquisitive Strategies Promote Resistance and Temporal Stability of Semiarid Grasslands - Pu Yan; Nianpeng He; Marcos Fernández‐Martínez; Xian Yang; Yiping Zuo; Hao Zhang; Jing Wang; Shiping Chen; Jian Song; Guoyong Li; Enrique Valencia; Shiqiang Wan; et al. (Ecology Letters, 2025)
Among ecologists, it is widely believed that conservative growth strategies of plants are crucial for sustaining ecosystem stability, while the potential stabilising role of acquisitive strategies has received little attention. We investigated the relationships between plant traits and three stability dimensions—temporal stability, resistance and resilience—using two complementary datasets from drought‐affected semi‐arid grasslands: a temporal plant community survey from a single site and a 1000‐km transect survey with satellite‐derived productivity estimates. We found strikingly consistent patterns from the two datasets, with grasslands dominated by acquisitive strategies exhibiting greater resistance and temporal stability of productivity. Acquisitive strategies enhance stability by facilitating drought escape and avoidance, rather than drought tolerance typically associated with conservative strategies. These results highlight the important but underappreciated role of acquisitive strategies in enhancing ecosystem resistance to disturbances and maintaining temporal stability in semi‐arid grasslands.

Inhibition of platelet activation process upon tris (2-chloroethyl) phosphate exposure: Role of PFKP-mediated glycolysis and the pentose phosphate pathway - Ziyuan Li; Pu Chen; Yongfeng Lin; Jingxu Zhang; Jian Ding; Rifat Zubair Ahmed; Xiaoting Jin; Yuxin Zheng (Environmental Pollution, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Implant coating for promoted postoperative bone regeneration via cascade Reaction-Mediated microenvironment reprogramming - Bing Yan; Rurong Lin; Chongyin Qiu; Wei Sun; Xiaogang Ma; Jianxing Huang; Shuai Liu; Haifeng Liang; Chengzhong Xu; Chunyi Pu; Xiaojing Liu; Bo Yu; et al. (Chemical Engineering Journal, 2025)

Versatile poly (deep eutectic solvents) electroactive chitosan eutectogel for infected wound healing and monitoring administration - Shuai Liu; Jiamian Zhan; Zhenyu Liu; Xiaoying Tan; Jianxing Huang; Chunyi Pu; Rurong Lin; Yu Chen; Qi Luo; Xiaozhong Qiu; Honghao Hou (Carbohydrate Polymers, 2025)

Dissolved organic carbon can alter coastal sediment phosphorus dynamic: Effects of different carbon forms and concentrations - Shuo-Nan Ma; Xu-Meng Dong; Ji-Lin Xu; Chun-Pu Zhao; Miao Liu; Hai-Jun Wang; Erik Jeppesen (Chemosphere, 2025)

Performance and calculation of trussed concrete-filled steel tubular (CFST) hybrid structures subjected to bending - Zhan-Shuo Liang; Lin-Hai Han; Pu Wang (Engineering Structures, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

Thermodynamic mechanism of silica dosage and temperature on phase composition of well cement at high temperature and its impact on macro-properties - Huiting Liu; Tong Li; Jiaying Zhang; Pu Xu; Xiujian Xia; Yongjin Yu; Lin Liu; Huisu Chen (Applied Geochemistry, 2025)

Utilization of drinking water treatment sludge with coal fly ash to make permeable bricks for low impact development - Pu Li; Feiyun Sun; Ye Dong; Lei Wen; Lin Lin; Xiao-yan LI (Resources, Conservation and Recycling, 2025)

Correlation study between structural parameters of droplets and rheological properties of O/W high internal phase Pickering emulsions above the closest packing density - Chenzhi Wang; Yan Li; Wei Xiong; Qiang Liang; Xin Hua; Pu Xuan; Wei Lin; Yingzheng Yao (Food Hydrocolloids, 2025)

Structural analysis and accelerating wound healing function of a novel galactosylated glycosaminoglycan from the snail Helix lucorum - Ya Li; Xingzi Wang; Jiangyan Chen; Luyun Sun; Debing Pu; Lisha Lin; Lan Luo; Xi Gong; Junxue Pu; Mingyi Wu (Carbohydrate Polymers, 2025)

Spatiotemporal distribution patterns of large and medium-sized mammals in a biodiversity hotspot: mplications for conservation - Wenqiang Hu; Xueyou Li; Kenneth Otieno Onditi; Hongjiao Wang; Wenyu Song; Zhechang Hu; Changzhe Pu; Mingjing Pu; Yun Xiong; Suhua Yang; Lin Zhu; Jianqiang Yin; et al. (Biological Conservation, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

Treadmill Exercise Enhances Post-Stroke Functional Recovery in Mice via the CX3CL1/CX3CR1 Signaling Pathway - Yangyang Ge; Xiaoke Dou; Pu Chen; Jiayi Chen; Maosha Dai; Shanglong Yao; Yun Lin (Molecular Neurobiology, 2025)

Multi-coal seam mining-induced collapse and deformation evolution of high steep slopes of the Shaomi collapse, Guizhou, China - Baiquan Shen; Weihua Zhao; Jianjun Zhao; Qingmiao Li; Huabo Xiao; Zuoyao Pu; Hanlei Peng; Lin Tan (Landslides, 2025)

Molecular phylogenetic and estimation of evolutionary divergence and biogeography of the family Schizoparmaceae and allied families (Diaporthales, Ascomycota) - Taichang Mu; Yongsheng Lin; Huili Pu; Nemat O. Keyhani; Yuxiao Dang; Huajun Lv; Zhiying Zhao; Zhiang Heng; Ziyi Wu; Chengjie Xiong; Longbing Lin; Yuxi Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Automatic identification of saltating tracks driven by strong wind in high-speed video using multiple statistical quantities of instant particle velocity - Hongji Zhou; Fanmin Mei; Chuan Lin; Mengjie Pu; Aiguo Xi; Jinguang Chen; Jin Su; Zhibao Dong (Aeolian Research, 2024)

High mobility emissive BN-Embedded Dinaphthalenyl anthracene for organic light emitting transistors - Ze-Wei Lin; Pu Wang; Sheng-Hong Zhao; Yun-Tao Ding; Huanli Dong; Hao-Li Zhang (Chemical Engineering Journal, 2024)

Advanced functional carbon electrode for ultra-sensitive detection of hexavalent chromium in water: Performance, mechanism, and application - Zeyu Liu; Yao Liu; Lin He; Qiang Xue; Jianwei Zhao; Shengyan Pu (Chemical Engineering Journal, 2024)

Mechanistic insights and performance evaluation of ZnFe-Modified bovine manure biochar in activating peroxymonosulfate for efficient thiamethoxam degradation: A combined DFT calculation and degradation pathway analysis - Qiao Zhou; Shenglan Wang; Chao Zhang; Yuechi Lin; Mengjie Pu; Xinzhi Wang; Shibo Zhu; Huizhen Chen; Zhe Zhang; Mingzhi Huang (Chemical Engineering Journal, 2024)

Genomic Investigation of a Rhizosphere Isolate, Streptomyces sp. JL1001, Associated with Polygonatum cyrtonema Hua - Lin Jiang; Zixian Zeng; Zhi Wang; Min Tang; Sai Jiang; Qingxian Ma; Zhong Wang; Dian Peng; Shunxiang Li; Hong Pu (Current Microbiology, 2024)

Microplasma-induced in situ rapid synthesis of CoSe nanosphere@N-doped polymeric carbon dots derived from ZIF-67 for highly sensitive dopamine detection - Lin Zhang; Junchun Guo; Ming Yuan; Yao Xu; Ziyu Pu; Chao Tan; Qian Wang; Xiaoli Xiong (Analytica Chimica Acta, 2024)

Nrf2 affects DNA damage repair and cell apoptosis through regulating HR and the intrinsic Caspase-dependent apoptosis pathway in TK6 cells exposed to hydroquinone - Lin Chen; Pu Guo; Lu Zhai; Lingxue Yu; Delong Zhu; Xiaoyi Hu; Zhuanzhuan Li; Yuting Chen; Qian Sun; Lei Sun; Hao Luo; Huanwen Tang (Toxicology in Vitro, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Platinum-dependent 2H-to-1T phases conversion of MoS2 nanosheets growing on cross-interlocking porous carbon for boosting hydrogen evolution reaction - Lulu Chen; Yichao Huang; Jiajun Wang; Meihong Liao; Sixuan Huang; Hanqing Cai; Lin Wang; Lianming Zhao; Ning Pu; Zhuangjun Fan (Chemical Engineering Journal, 2024)

Diterpenoid alkaloids from Delphinium trichophorum - Shuai Huang; Jian-Zhu Wang; Yang-Li Pu; Yu-Yan Liu; Ying Chen; Lin Chen; Xian-Li Zhou (Phytochemistry, 2024)

Assessment of the antimicrobial and immunomodulatory activity of QS-CATH, a promising therapeutic agent isolated from the Chinese spiny frogs (Quasipaa spinosa) - Wei-Cheng Zheng; Xiao-Yun Cheng; Yu-Hui Tao; Yue-Song Mao; Cheng-Pu Lu; Zhi-Hua Lin; Jie Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

A novel nitric oxide-driven nanomotor for synergistic treatment of ischaemic stroke: Enhanced deep brain penetration and therapeutic efficacy - Zhicheng Xiao; Yi Li; Ting Chen; Chenchen Xie; Jun Liao; Pu Lin; Zhe-Sheng Chen; Yan Qiu; Jian Cai; Chuan Zhang; Tingfang Wang (Chemical Engineering Journal, 2024)

Small molecule perylene diimide derivatives with different bay site modifications as cathode interface layers for organic solar cells - Yanyan Wang; Dan Zhou; Senmei Lan; Jianwei Quan; Fang Wang; Lin Hu; Ruizhi Lv; Yujie Pu; Haitao Xu; Yongfen Tong; Bin Hu; Zhentian Xu; et al. (Chemical Engineering Journal, 2024)

The Meso-Tethys Ocean: The nature, extension and spatial-temporal evolution - Jian-Jun Fan; Bo-Chuan Zhang; Jian-Bo Zhou; Yaoling Niu; Si-Lin Sun; Jun-Pu Lv; Yang Wang; Yu-Jie Hao (Earth-Science Reviews, 2024)

Single-cell characterization of major components of plant cell walls in situ by Raman spectroscopy - Yujian Li; Weiwei Shen; Xi Zhang; Yaning Cui; Yuanyuan Zhao; Yayu Guo; Xiaojuan Li; Shuizhong Wang; Guoyong Song; Pu Wang; Jianfeng Ma; Jinxing Lin (Science China Life Sciences, 2024)

Relay intercropping boosts soybean recovery growth and delays nodule senescence to achieve yield advantages - Ping Chen; Benchuan Zheng; Huan Yang; Qing Du; Zhidan Fu; Kai Luo; Yilin Li; Ping Lin; Xihong Peng; Tian Pu; Yushan Wu; Xiaochun Wang; et al. (Agriculture, Ecosystems & Environment, 2024)

Nonphytotoxic and pH-responsive ZnO-ZIF‑8 loaded with honokiol as a “nanoweapon” effectively controls the soil-borne bacterial pathogen Ralstonia solanacearum - Xunliang Huang; Yue Xing; Hao Jiang; Ya Pu; Song Yang; Zhensheng Kang; Lin Cai (Journal of Hazardous Materials, 2024)

Influence of continuous phase evolution of non-aqueous phase liquid on the retention and transport of coexistence perfluorooctanoic acid in saturated porous media - Peng Wang; Zheng Yan; Xiang Lin; Bingrui Yang; Wen Zhang; Dongsheng Wu; Zhilin Guo; Shengyan Pu (Journal of Hydrology, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Boosted outputs and robustness of polymeric tribovoltaic nanogenerator through secondary doping - Jia Meng; Chuntao Lan; Chongxiang Pan; Jun Yang; Xiong Pu; Zhong Lin Wang (Chemical Engineering Journal, 2024)

Two new monoterpene esters from Illigera paviflora Dunn roots - Meng-Yuan Jiang; Xiao-Yun Pu; Wen-Ting Li; Juan Liu; Xiao-Li Zeng; Hong-Rui Li; Xi-Shan Bai; Lin Hu; Xiang-Zhong Huang (Natural Product Research, 2024)

Carbon emissions of urban rail transit in Chinese cities: A comprehensive analysis - Jing Pu; Chen Cai; Ru Guo; Jiangchuan Su; Ruimin Lin; Jia Liu; Kaiming Peng; Chaoguang Huang; Xiangfeng Huang (Science of The Total Environment, 2024)

Velocity estimation method for high-spinning vehicle based on a side-mounted single patch antenna - Wenyang Pu; Qiang Shen; Zilong Deng; Hanyu Wang; Hongyun Li; Ziyang Lin (GPS Solutions, 2024)

Investigations of the Formation Mechanism and Pressure Pulsation Characteristics of Pipeline Gas-Liquid Slug Flows - Gaoan Zheng; Pu Xu; Lin Li; Xinghua Fan (Journal of Marine Science and Engineering, 2024)
The pipeline system is widely used in marine engineering, and the formation mechanism and flow patterns of two-phase slug flows are of great significance for the optimal design of and vibration prevention in a complex pipeline system. Aiming at the above problems, this paper proposes a modeling and solving method for gas-liquid slug flows. First, a VOF-PLIC-based coupling gas-liquid slug flow transport model is conducted. Second, to reduce the fuzzy boundary between the gas-liquid coupling interfaces, an artificial compression term is added to the transport equations, and the formation and evolution mechanism of severe slugging flow in piping systems is investigated. The pressure pulsation and gas content characteristics of the gas-liquid coupling process are explored. Research results found that the slugging phenomenon occurs at the gas-liquid interface, where liquid slugging frequency reaches its peak. The pipeline system has prominent periodic characteristics of the slugging phenomenon, and the period decreases when the gas-phase converted speed rises; pressure fluctuation amplitude increases, and the gas-phase velocity change is the inducing factor for the drastic change of pressure fluctuation. The research results can offer theoretical references for optimal designs of and vibration prevention in marine pipeline systems.

Three chemosensory proteins enriched in antennae and tarsi of Rhaphuma horsfieldi differentially contribute to the binding of insecticides - Yu-Juan Yao; Ning-Na Yin; Lin-Mei Pu; An-Jing Yang; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2024)

Genome-wide DNA methylation of lesional and peri-lesional skin in vitiligo: a comparative and integrated analysis of multi-omics in Chinese population - Lin Liu; Yuzhou Xue; Yuxin Li; Yangmei Chen; Xingyu Pan; Yujing Huang; Tingqiao Chen; Judan Zhong; Xinyi Shao; Yihuan Pu; Jin Chen (Human Genetics, 2024)

A ratiometric fluorescent probe based on the FRET platform for the detection of sulfur dioxide derivatives and viscosity - Feng-Ting Liu; Peng-Fei Jiang; Yan-Pu Wang; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2024)

Suggested method of utilizing soil arching for optimizing the design of strutted excavations - Ben-Guo He; Bo Lin; Hong-Pu Li; Shi-Qi Zhu (Tunnelling and Underground Space Technology, 2024)

Major contributions of agricultural management practices to topsoil organic carbon distribution and accumulation in croplands of East China over three decades - Yue Pu; Lin Yang; Lei Zhang; Haili Huang; Ganlin Zhang; Chenghu Zhou (Agriculture, Ecosystems & Environment, 2024)

Linked mutations within the pathogenicity locus of Clostridioides difficile increase virulence - Qianyun Lin; Zitong Li; Haoran Ke; Jiaxi Fei; Ting Zhang; Pu Wang; Ye Chen (Infectious Diseases, 2023)

Emission characteristics of naphthalene from ship exhausts under global sulfur cap - Chin-Ko Yeh; Fu-Ming Tzu; Po-Yang Chen; Hsueh-Chen Shen; Chung-Shin Yuan; Chitsan Lin; Han-Pin Pu; Huu Hao Ngo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

MiR-7-5p targeted Rb regulating cell cycle is involved in hydroquinone-induced malignant progression in human lymphoblastoid TK6 cells - Lu Zhai; Yuting Gao; Zheming Cui; Lin Chen; Lingxue Yu; Pu Guo; Delong Zhu; Huanwen Tang; Xin Liu; Hao Luo (Food and Chemical Toxicology, 2023)

A shared role of the myocardin-family transcriptional coactivators in cardiomyocyte maturation - Yuxuan Guo; Yangpo Cao; Blake D. Jardin; Neil Mazumdar; Congting Guo; Luzi Yang; Junsen Lin; Zhan Chen; Qing Ma; Mingming Zhao; Erdan Dong; William T. Pu (Science China Life Sciences, 2023)

Study of Mechanical Properties of Three-Dimensional Framed Plate Protective Structures with Negative Poisson’s Ratio - Weijun Lin; Mengzhen Li; Pu Li; Qianning Li; Wei Chen (Journal of Marine Science and Engineering, 2023)
In this paper, the negative Poisson’s ratio and rigidity of a protective structure are improved to allow the structure to exert a negative Poisson’s ratio effect in multiple directions and to enhance the structural load-carrying capacity. Therefore, a 3D framed plate honeycomb is designed on the basis of a traditional 2D negative Poisson’s ratio honeycomb. The Poisson’s ratio and modulus of elasticity are derived, and the equivalent mechanics model (EMM) of a 3D framed plate protective structure is established by combining bending deformation, shear deformation, and compression deformation. To verify the validity of the equivalent mechanics model (EMM), a compression test and numerical simulation study are carried out by combining 3D printing technology and numerical simulation methods. In addition, the effects of structural parameters on the modulus of elasticity, negative Poisson’s ratio, and other mechanical properties are discussed. The results show that, under vertical loading, the equivalent Poisson’s ratio and the modulus of elasticity of the cell elements decrease with the increase in the ratios of the lengths of the cell element walls in the upper and lower planes to the length of the diagonal cell element in the concave direction. In addition, it is shown that the elastic modulus increases with increasing concave angle and thickness. Moreover, under lateral loading, the equivalent Poisson’s ratio of the cell elements increases with the ratios of the lengths of the upper and lower planar cell element walls to the length of the diagonal cell element walls, with the angle of concavity and with the thickness of the plate frame, while the modulus of elasticity of the cell elements exhibits the opposite trend and decreases with the thickness of the framed plate structure.

Analysis of the driving factors of the change of erosion-deposition in the Minjiang Estuary, Southeast China - Xiaohe Lai; Jianping Jia; Yuebao Hou; Beihan Jiang; Chuan Lin; Xinlu Lin; Pu Xu; Cheng Chen; Jun Jiang; Yan Liu; Wen Wei (Frontiers in Marine Science, 2023)
Understanding the evolution and driving factors of sedimentation and erosion at the mouths of small and medium-sized mountain streams during various periods is essential for regional spatial utilization, development, and sustainable economic growth. This is particularly important when considering the combined impact of climate change and human activities. This paper presents an analysis of the changes in sedimentation and erosion of mouth isobaths and underwater deltas over different periods using nautical chart data (1950-2019) and analyzes the factors driving changes in sedimentation and erosion during different periods from 1950 to 2020 based on the runoff-sediment discharge of the Minjiang River (MR) and extreme climate factors such as typhoons, especially the driving factors that caused a sudden change in the sedimentation and erosion process between 1998 and 2005. The results indicate that runoff-sediment characteristics are crucial in driving sedimentation and erosion changes. In the past 70 years, the underwater delta of the MRE has mainly experienced four stages: deposition (1950-1992) -erosion (1993-1998) -deposition (1998-2011) -erosion (2011-2019). Taking the impoundment operation of the Shuikou Reservoir in 1993 as the node, the sediment load of the Minjiang River into the sea began to decrease sharply, and then the estuary quickly showed a state of erosion. The change of sediment flux into the sea is the main driving factor for the evolution of erosion and deposition in the Minjiang River Estuary (MRE). The critical value of the erosion-deposition transition is about 570.3 × 10 4 t/yr. After the estuary entered a state of erosion in 1993-1998, significant siltation suddenly occurred in 1998-2005. The reason for the siltation in this period may be related to the frequent transit typhoons and flood events in 1998-2005. Therefore, the change of river sediment supply into the sea is the main driving factor controlling the erosion and deposition evolution of the Minjiang River estuary on a long time scale of more than 10 years, which reflects the influence of large-scale human activities on the river and estuary area in the past half century. Extreme climate events are the incentive to adjust the estuary landform in the short term. Extreme climate events will not fundamentally change the process of estuarine geomorphological evolution under the background of sediment supply reduction.

Measuring and modeling the effects of green barriers on the spatial distribution of fine particulate matter at roadside - Xin Chen; Jie Wu; Wenbin Yang; Zhanyong Wang; Shuting Chen; Xisheng Hu; Kaifa Lu; Zhongmou Fan; Mei Lin; Pu Chen (Urban Climate, 2023)

In situ enrichment of sulphate-reducing microbial communities with different carbon sources stimulating the acid mine drainage sediments - Zhuo-hui Wu; Xiao-dan Yang; Li-ying Huang; Shi-lin Li; Fei-yun Xia; Yong-zhi Qiu; Xin-zhu Yi; Pu Jia; Bin Liao; Jie-Liang Liang; Wen-sheng Shu; Jin-tian Li (Science of The Total Environment, 2023)

Microplastic contamination in fish: Critical review and assessment of data quality - Xiaohui Lin; Aoife A. Gowen; Hongbin Pu; Jun-Li Xu (Food Control, 2023)

Effect of the inoculation of Phanerochaete chrysosporium on nitrogen migration and organic matter conversion during electrolytic manganese residue composting - Xiangyu Peng; Ming Yan; Qingqing Xie; Lan Gao; Xiaojuan Pu; Yukui Fu; Hanwen Liu; Min Cheng; Piao Xu; Danlian Huang; Lin Tang (Bioresource Technology, 2023)

Method for calculating the uplift capacity of a circular anchor plate at arbitrary depth in sand - Wei Hu; Zhi Lin; Hui Wang; Pu Zhao; Dongxue Hao; Jian Gong (Ocean Engineering, 2023)

New advance in biorenewable FDCA-based polyesters: Multiple scale-up from lab bench to pilot plant - Bo Wang; Zhu Tu; Xinyuan Zhang; Lin Sang; Wentao Chan; Lei Wang; Xinming Pu; Feng Ling; Min Qi; Zhiyong Wei (Chemical Engineering Journal, 2023)

Efficacy of transplant insecticides against black cutworm Agrotis ipsilon (Lepidoptera: Noctuidae) in tobacco - Pingping Liu; Jingxin Zhang; Huifang Shen; Qiyun Yang; Xiaoming Pu; Dayuan Sun; Baiyi Ge; Birun Lin (Crop Protection, 2023)

Environmental occurrence and ecotoxicity of aquaculture-derived plastic leachates - Lin Lin; Yuxiong Huang; Pu Wang; Ciara Chun Chen; Wei Qian; Xiaoshan Zhu; Xiangrong Xu (Journal of Hazardous Materials, 2023)

A gluten degrading probiotic Bacillus subtilis LZU-GM relieve adverse effect of gluten additive food and balances gut microbiota in mice - Aman Khan; Shiqing Li; Huawen Han; Wei-Lin Jin; Zhenmin Ling; Jing Ji; Shazia Iram; Pu Liu; Sa Xiao; El-Sayed Salama; Xiangkai Li (Food Research International, 2023)

A rapid and effective method for obtaining ardicrenin from Ardisia crenata Sims var. bicolor plants - Zhen Lin; Xiuling Yang; Lin Li; Chunyan Ma; Lingjuan Kong; Huancheng Li; Shican Xiong; Haiyan Zhong; Shangrao Pu; Fang Liang; Ju Hu (Brazilian Journal of Botany, 2023)

New evidence of the Hoyle-like structure in 16O - Jiahao Chen; Yanlin Ye; Kai Ma; Jiaxing Han; Dongxi Wang; Chengjian Lin; Huiming Jia; Lei Yang; Gen Li; Lisheng Yang; Ziyao Hu; Zhiwei Tan; et al. (Science Bulletin, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

OsCIP1, a secreted protein, binds to and stabilizes OsCR4 to promote aleurone layer development, seed germination and early seedling growth in rice - Lin-Lin Yan; Jing Mi; Can-Can Shen; Rong Qian; Jiao Wang; Cui-Xia Pu; Ying Sun (Plant Science, 2023)

Phytomelatonin interferes with flavonols biosynthesis to regulate ROS production and stomatal closure in tobacco - Lin Xiao; Wenna Ma; Jiarong Zhang; Xiaojun Pu; Zed Rengel; Zhongbang Song; Qi Chen (Journal of Plant Physiology, 2023)

The shadows hang over immunotherapy-neutrophil extracellular traps in cancer - Dan Pu; Liyuan Yin; Xiaoqian Zhai; Ruoxiang Wang; Lin Huang; Qiang Wu; Lingling Zhu; Yuwen Zhou; Qinghua Zhou; Lu Li (Science China Life Sciences, 2023)

Nano-Fe3O4 coated on carbon monolith for anode enhancement in microbial fuel cells - Yini Chen; Fan Zhao; Yu Pu; Xiangyu Lin; Haoran Yin; Xinhua Tang (Journal of Environmental Chemical Engineering, 2023)

Complete genome of Sphingomonas paucimobilis ZJSH1, an endophytic bacterium from Dendrobium officinale with stress resistance and growth promotion potential - Jin Li; Hangtao Wu; Qian Pu; Chu Zhang; Ying Chen; Zhengxin Lin; Xiufang Hu; Ou Li (Archives of Microbiology, 2023)

Genome-wide identification, structural and evolutionary characteristics, and expression analysis of aquaporin gene family members in Mercenaria mercenaria - Cong Zhou; Zhi-shu Lin; Ying Shi; Jie Feng; Zhi Hu; Mei-jie Yang; Pu Shi; Yong-ren Li; Yong-jun Guo; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
Aquaporins (AQPs) are highly-selective transmembrane water transporters that are involved in the adaptation to environmental challenges. However, the structure, function, and evolution of AQPs in bivalves remain largely unknown. In this study, AQP gene family members were identified in nine bivalve species, and their abundance rangs from 7 to 15. Nine AQPs (MmAQPs) were identified in the genome of hard clam ( Mercenaria mercenaria ), which is a euryhaline bivalve that has evolved sophisticated osmoregulatory mechanisms and salinity adaptation. Structurally, all MmAQPs contain 6 or 12 transmembrane α-helices, a major intrinsic protein (MIP) domain, and 2 asparagine-proline-alanine (NPA) motifs. MmAQPs were classified into three subfamilies based on phylogenetic analysis: AQP1-like, AQP3-like, and AQP8-like. No AQP11-like subfamily member was identified in the genome of hard clam. Tandem duplication resulted in a lineage-specific expansion in AQP8-like subfamily in hard clams. MmAQP8 genes showed different expression sensitivity to different environmental stressors. The gene expression patterns of three MmAQP8 were similar under heat, hypoxia, and air exposure stress, but differed greatly under salinity stress, indicating that tandem duplication events may accelerate the functional divergence of AQP8 genes in hard clams. AQP3-like members may have undergone gene loss during evolution, resulting in weakened glycerol and urea penetration in hard clams. Three orthologs of MmAQPs were detected in the genomes of Cyclina sinensis and Archivesica marissinica through synteny analyses. Tissue expression profiles showed that MmAQP genes were highly expressed in the foot and hepatopancreas. Under environmental stress, the expression levels of most of the MmAQP genes changed significantly to maintain metabolic homeostasis. Several MmAQP genes were downregulated to reduce water permeability under salinity and air exposure stress. Several MmAQP genes were significantly upregulated to promote the transmembrane transport of ammonia and reactive oxygen species and activate anti-apoptotic responses to resist stress. This study provides a comprehensive understanding of the AQP gene family in hard clams, and lays a foundation for further studies to explore the functions of AQPs in bivalves.

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

RNA-seq analysis reveals the effect of the metamorphic cue (juvenile oysters) on the Rapana venosa larvae - Mei-Jie Yang; Ying Shi; Zhi-Shu Lin; Pu Shi; Zhi Hu; Cong Zhou; Peng-Peng Hu; Zheng-Lin Yu; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
As a vital developmental event, metamorphosis controls the population dynamics of most marine invertebrates and affects the breeding of economic shellfish. Rapana venosa is an economically important species in China, but artificial aquaculture has hampered its metamorphosis process. Previous studies have found that juvenile oysters can effectively induce the metamorphosis of R. venosa , but the specific induction mechanism is not clear. Here, we investigated the mechanism underlying the response of R. venosa to juvenile oysters through the RNA-seq analysis. In this study, the gene set responses to metamorphosis cues (juvenile oysters) in R. venosa were identified, and GO and KEGG enrichment analyses were further performed on these gene sets. The results showed that the expression of the prototype of the class of immediate early genes, the transcription factor AP-1, was rapidly and significantly increased, and the molecular chaperone of NOS, HSP90, exhibited lower expression in the M12 group than in the control group. In contrast, the expression of inhibitors of apoptosis (IAPs) was significantly increased upon exposure to juvenile oysters. Additionally, the Wnt signaling pathway and MAPK signaling pathway were enriched in the trend analysis. These pathways may also play critical regulatory roles in the response to juvenile oysters. Taken together, the results show that competent larvae rapidly respond to the inducing effects of oysters via some immediate early genes, such as the transcription factor AP-1, which may further regulate downstream pathways such as the MAPK signaling pathway to cause subsequent changes, including a decrease in HSP90 and an increase in IAPs. These changes together may regulate the metamorphosis of R. venosa . This study provides further evidence that juvenile oysters are the metamorphosis cues of R. venosa , which may enhance our understanding of the metamorphosis mechanism in this marine invertebrate.

One-step coaxial spinning of core-sheath hydrogel fibers for stretchable ionic strain sensors - Hui Wu; Lin Wang; Hengyi Lou; Junmin Wan; Xiong Pu (Chemical Engineering Journal, 2023)

Low 15d-PGJ2 status is associated with oxidative stress in chronic obstructive pulmonary disease patients - Shi-Xue Ma; Guo-Fang Xie; Pu Fang; Min-Min Tang; You-Peng Deng; Yu-Jin Lu; Wei Cao; Lin Fu (Inflammation Research, 2023)

The effect of underwater supplemental light on the growth of V.spinulosa Yan and the restoration process of water - Jinshan Zhao; Pu Yang; Yuye Lin; Xiaoyao Zhu; Jiaxin Wang; Xinyu Gan; Xiangyong Zheng; Min Zhao; Chunzhen Fan; Linna Du; Huanyi Miu (Process Safety and Environmental Protection, 2023)

Effects of wetland, tide, and season on benthic biofilms and related sediment properties in mangrove ecosystems - Lihua Yang; Qian Yang; Li Lin; Tiangang Luan; Qiong Yang; Pu Li; Nora F. Y. Tam (Frontiers in Marine Science, 2022)
Sediment biofilms, mainly composed of diatoms, bacteria, and related extracellular polymeric substances (EPS), play important roles in mangrove ecosystems. In order to better understand the microbial biodiversity in marine environment, this study aims to clarify the effects of wetland, season, and tide on benthic biofilms and related sediment properties based on in situ investigation in two mangrove wetlands (Futian and Qi’ao) in the Pearl River Estuary, South China. Owing to the tide current, the northeastern Futian is more influenced by seawater than the southwestern Qi’ao. As a consequence of the salinity-driven accumulation of nutrients in sediments, Futian is more eutrophic than Qi’ao. Compared to Qi’ao, the higher nutrimental condition in Futian conserves higher abundance of eutrophic indicators of Nitzschia and Cyclotella , which results in higher values of all pigments and bound polysaccharide with varied monosaccharide composition. Compared to the seaward site, the landward site has higher abundance of benthic (pennate) diatoms but lower abundance of planktonic (centric) diatoms due to the varied settling velocity by tidal disturbance. This varied diatom composition leads to higher levels of bound polysaccharide and more monosaccharides in the landward site than in the seaward site. Compared to late spring (March), early summer (May) appears to have similar diatom abundance but more EPS fractions (except bound protein) and monosaccharides due to the higher level of light intensity and temperature. The observed lower bacterial abundance in May than in March might be due to the higher predation pressure. The baseline data on biofilm compositions in mangrove ecosystems from this study can improve the understanding of microbial biodiversity in response to the tidal, temporal, and spatial changes.

Effects of Fdft 1 gene silencing and VD3 intervention on lung injury in hypoxia-stressed rats - Xiaoyan Pu; Xue Lin; Yinglian Qi; Yinglian Li; Tiantian Li; Yang Liu; Dengbang Wei (Genes & Genomics, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Meta-analysis of the associations of IMPDH and UGT1A9 polymorphisms with rejection in kidney transplant recipients taking mycophenolic acid - Lin Cheng; Pu Yao; Bangbi Weng; Ming Yang; Qian Wang (European Journal of Clinical Pharmacology, 2022)

Experimental investigation on debris flow resistance and entrainment characteristics: effects of the erodible bed with discontinuous grading - Pu Li; Jia-ding Wang; Kai-heng Hu; Hai-jun Qiu; Jia-lin Xie (Journal of Mountain Science, 2022)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

Undescribed benzophenone and xanthones from cave-derived Streptomyces sp. CB09001 - Lin Jiang; Jingxi Xiang; Saibin Zhu; Danfeng Tang; Bang Gong; Hong Pu; Yanwen Duan; Yong Huang (Natural Product Research, 2022)

Functional traits explain the consistent resistance of biodiversity to plant invasion under nitrogen enrichment - Shao‐peng Li; Pu Jia; Shu‐ya Fan; Yingtong Wu; Xiang Liu; Yani Meng; Yue Li; Wen‐sheng Shu; Jin‐tian Li; Lin Jiang (Ecology Letters, 2022)
Elton's biotic resistance hypothesis, which posits that diverse communities should be more resistant to biological invasions, has received considerable experimental support. However, it remains unclear whether such a negative diversity–invasibility relationship would persist under anthropogenic environmental change. By using the common ragweed ( Ambrosia artemisiifolia ) as a model invader, our 4‐year grassland experiment demonstrated consistently negative relationships between resident species diversity and community invasibility, irrespective of nitrogen addition, a result further supported by a meta‐analysis. Importantly, our experiment showed that plant diversity consistently resisted invasion simultaneously through increased resident biomass, increased trait dissimilarity among residents, and increased community‐weighted means of resource‐conservative traits that strongly resist invasion, pointing to the importance of both trait complementarity and sampling effects for invasion resistance even under resource enrichment. Our study provides unique evidence that considering species’ functional traits can help further our understanding of biotic resistance to biological invasions in a changing environment.

A five-year investigation of water quality and heavy metal mass flux of an industrially affected river - Gavin Yeh; Chitsan Lin; Duy-Hieu Nguyen; Hong-Giang Hoang; Jian-Chuan Shern; Pu-Jen Hsiao (Environmental Science and Pollution Research, 2022)

A Preliminary Study on Silver Isotopic Composition in Polymetallic Ore Deposits in Eastern China - Ge Dong; Hai-Zhen Wei; Yuanfeng Zhu; Xi Liu; Qi Guo; Wei Pu; Yibo Lin; Junlin Wang (Journal of Earth Science, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Efficacy and safety between early use and late use of celecoxib in hip osteoarthritis patients who receive total hip arthroplasty: a randomized, controlled study - Chunxue Pu; Xue Jiang; Yuanxin Sun; Hui Lin; Shaochen Li (Inflammopharmacology, 2021)

Analysis of the starch properties in tetraploid wheat–Aegilops sharonensis amphidiploid - Qing Li; Xuteng Zhang; Na Lin; Guzmán Carlos; Jingyu Lan; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Wei Li; Zhien Pu; et al. (Cereal Research Communications, 2021)

Trophic Plasticity of Bombay Duck (Harpadon nehereus) in the South-Central East China Sea Based on Stable Isotope Evidence - Pu-Qing Song; Hu-Shun Zhang; Xin-Qing Zheng; Yuan-Yuan Li; Long-Shan Lin; Yuan Li (Frontiers in Marine Science, 2021)
High trophic plasticity is often invoked to explain the successful expansion of many aquatic species. Bombay duck (BD) outcompete other traditionally commercial fishes in the East China Sea (ECS) in recent years, displaying a continuous and sharp increase of catches, however, little is known whether the competition advantage of BD was related to its trophic plasticity. Using stable isotope analysis (SIA), we investigated the trophic ecology of BD in the south-central ECS in two periods. Significant differences in δ 13 C and δ 15 N values were found between sampling months and among body sizes. Modal (95% credibility limits) estimation showed that BD’s trophic position (TP) gradually increased from 3.56 (3.31–3.82) in G1 (120–150 mm for body size) to 4.09 (3.69–4.50) in G5 (241–270 mm) in November, and from 3.37 (2.92–3.88) in G2 (151–180 mm) to 3.66 (3.07–4.23) in G4 (211–240 mm) in April, respectively, suggesting obvious ontogenetic variation of δ 15 N and TP. More importantly, the TP of BD within the same body size showed wide amplitude, indicating BD possess high trophic plasticity, and can capture prey from low to high trophic levels. Further quantitative analysis based on the MixSIAR model showed that BD mainly fed on zooplankton and fish, but its feeding habit was characterized by the consumption of gradually reduced zooplankton and increased fish associated with increased body size. Interestingly, the fish’s contribution to BD showed obvious seasonal variation. It can be explained by varied food availability in ECS. Relatively low fish prey in April forced BD to adjust its diet, adding the ingestion of shrimps and cephalopods corresponding to temporal variations in food availability. The present study provides the evidence that high trophic plasticity exists in the feeding strategy of BD, which is reflected in the ability to adjust the feeding preference according to nutritional needs and food environmental changes; thus, it is competitively advantageous and may partly explain why BD is becoming the predominant species and displays an extensive distribution in the ECS.

An Automatic Method for Tree Species Point Cloud Segmentation Based on Deep Learning - Lin Pu; Jiabin Xv; Fei Deng (Journal of the Indian Society of Remote Sensing, 2021)

Antimicrobial Activity of Natural Plant Compound Carvacrol Against Soft Rot Disease Agent Dickeya zeae - Shangbo Jiang; Jingxin Zhang; Qiyun Yang; Dayuan Sun; Xiaoming Pu; Huifang Shen; Qiqin Li; Zhongwen Wang; Birun Lin (Current Microbiology, 2021)

The Characteristic of Critical Genes in Neuroendocrine System and Their Regulation on Food Habit Transition and Metamorphosis of Veined Rapa Whelk Rapana venosa (Valenciennes, 1846) - Mei-Jie Yang; Jie Feng; Hao Song; Zheng-Lin Yu; Pu Shi; Jian Liang; Zhi Hu; Cong Zhou; Xiao-Lin Wang; Tao Zhang (Frontiers in Marine Science, 2021)
Metamorphosis is a critical developmental event in mollusks, and neuroendocrine system plays an essential role in this process. Rapana venosa is an economically important shellfish in China, but the artificial technology of R. venosa aquaculture is limited by metamorphosis. As a carnivorous gastropod, food habit transition makes the mechanism of R. venosa metamorphosis more complex. To investigate the changes in the neuroendocrine system and to reveal its role in regulating the food habit transition and metamorphosis of R. venosa , we cloned the cDNA sequences encoding 5-hydroxytryptamine receptor ( Rv-5HTR ), nitric oxide synthetase ( Rv-NOS ) and cholecystokinin receptor ( Rv-CCKR ), and investigated their expression by quantitative real-time PCR analysis, and explore the spatio-temporal changes of 5-HT protein expression using Immunohistochemical (IHC) analysis. The expression of the three geens was significantly increased in the early intramembrane veliger stage, which indicates that the three genes are related to the development of digestive system. Additionally, expression of the three genes was decreased after metamorphosis, while Rv-NOS and Rv-CCKR were increasingly expressed in competent larvae, which may help the larvae find suitable environments and promote digestive system development for metamorphosis, and the result of 5-HT IHC analysis also reflects the development of neuroendocrine system. Furthermore, results show that CCK can effect the expression of digestive enzyme, NOS and 5-HT receptor. Finally, based on the present results, we hypothesized that CCK and CCK receptor may be critical regulatory factors of food habit transition and metamorphosis. These results might provide information on the development of neuroendocrine system of R. venosa , and new insight into the regulation of the food habit transition and metamorphosis of gastropods.

Why pendulum symmetry is absent from the cymose partial inflorescences of Cannaceae? Insights into the essential characteristic of cincinni - Xueyi Tian; Qianxia Yu; Canjia Lin; Tong Zhao; Pu Zou; Jingping Liao (Journal of Plant Research, 2021)

Nuclear envelope integrity, DNA replication, damage repair and genome stability - Wenjun Pu; Haihui Zhang; Peiwu Qin; Lin Deng (Genome Instability & Disease, 2021)

Genome-Wide Association Study Identifies Genomic Loci of Sex Determination and Gonadosomatic Index Traits in Large Yellow Croaker (Larimichthys crocea) - Huanling Lin; Zhixiong Zhou; Ji Zhao; Tao Zhou; Huaqiang Bai; Qiaozhen Ke; Fei Pu; Weiqiang Zheng; Peng Xu (Marine Biotechnology, 2021)

Syn-2, 3-diols and anti-inflammatory indole derivatives from Streptomyces sp. CB09001 - Lin Jiang; Hong Pu; Xiangjing Qin; Jianxin Liu; Zhongqing Wen; Yimin Huang; Jingxi Xiang; Yunxi Xiang; Jianhua Ju; Yanwen Duan; Yong Huang (Natural Product Research, 2021)

Complement Factor H Displays Opposite Expression Patterns Under Two Situations of Methamphetamine Administration: Acute Exposure and Chronic Dependence - Ming Lin; Jiamin Xu; Zhimin Liu; Liang Qin; Xiaodong Wang; Xiaoping Pu (Neuroscience Bulletin, 2020)

Protective mechanism of fdft1 in steroid hormone synthesis pathway in SD rats with acute hypoxic injury - Xue Lin; Haiyan Wang; Xiaoyan Pu (Genes & Genomics, 2020)

Genome-Wide Association Study of Body Shape-Related Traits in Large Yellow Croaker (Larimichthys crocea) - Shengnan Kong; Zhixiong Zhou; Tao Zhou; Ji Zhao; Lin Chen; Huanling Lin; Fei Pu; Qiaozhen Ke; Huaqiang Bai; Peng Xu (Marine Biotechnology, 2020)

Macrophage–NLRP3 Inflammasome Activation Exacerbates Cardiac Dysfunction after Ischemic Stroke in a Mouse Model of Diabetes - Hong-Bin Lin; Guan-Shan Wei; Feng-Xian Li; Wen-Jing Guo; Pu Hong; Ya-Qian Weng; Qian-Qian Zhang; Shi-Yuan Xu; Wen-Bin Liang; Zhi-Jian You; Hong-Fei Zhang (Neuroscience Bulletin, 2020)

Optimized methods for diffusive greenhouse gas flux analyses in inland waters - Lin Zhu; Jianghua Yu; Bryce Van Dam; Huayong Cao; Yinyu Pu; Wenqing Shi; Boqiang Qin (Environmental Science and Pollution Research, 2020)

Rock mass permeability classification schemes to facilitate groundwater availability assessment in mountainous areas: a case study in Jhuoshuei river basin of Taiwan - Shih-Meng Hsu; Jun-Pu Hsu; Chien-Chung Ke; Yen-Tsu Lin; Chi-Chao Huang (Geosciences Journal, 2020)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

Evaluation of the impact of karst depression-type impoundments on the underlying karst water systems in the Gejiu mining district, southern Yunnan, China - Hai-Yan Gao; Ze-Min Xu; Kun Wang; Zhe Ren; Kui Yang; Yong-Jun Tang; Lin Tian; Ji-Pu Chen (Bulletin of Engineering Geology and the Environment, 2019)

SIMULATION OF SOIL WATER CONTENT FOR IRRIGATION MANAGEMENT BASED ON ON‐FIELD AND CERES‐WHEAT SIMULATED DATA IN WINTER WHEAT IN THE NORTH CHINA PLAIN - Lili Zhou; Shuhua Liao; Zhimin Wang; Pu Wang; Haijun Yan; Yinghua Zhang; Li Zhang; Xue Zhao; Shan Lin; Shunli Zhou (Irrigation and Drainage, 2019)
Accurate forecasting of the soil water in crop growth is crucial for developing an irrigation management strategy and saving water resources. The CERES model can be used to quantitatively predict the soil water content (SWC), but its accuracy and stability should be improved. The objectives of this research were to assess the CERES‐Wheat model for its ability to simulate the SWC in the winter wheat growth season and to study the possibility of improving simulation accuracy by building a modified model through introducing on‐field data and simulated values of CERES‐Wheat. Field experiment data of the varieties ShiJiaZhuang 8 and JiMai 22 from three to four irrigation treatments conducted over 4 years were used to compare precision of the CERES‐Wheat model and the modified model for SWC in the North China Plain. On average across all soil layers between 20 and 120 cm and two winter wheat varieties, the NRMSE decreased from 20.3% with the CERES‐Wheat model to 13.2% with the modified model. The results showed that the further improvement of SWC based on on‐field data and simulated data of CERES‐Wheat may be possible. Application prospects of dynamic water management of the modified model by introducing on‐field data during the wheat growth season were also discussed. © 2019 John Wiley & Sons, Ltd.

Dynamic changes in histone modification are associated with upregulation of Hsf and rRNA genes during heat stress in maize seedlings - Haoli Hou; Lin Zhao; Xueke Zheng; Mayank Gautam; Mengxia Yue; Jiaqi Hou; Zhenfei Chen; Pu Wang; Lijia Li (Protoplasma, 2019)

Comparative analysis of a panel of biomarkers related to protein phosphatase 2A between laryngeal squamous cell carcinoma tissues and adjacent normal tissues - Han-ying Wang; Hui Yuan; Jing-hui Liu; Bei-lei Wang; Kai-lun Xu; Pu Huang; Zhi-hong Lin; Li-hong Xu (Journal of Zhejiang University-SCIENCE B, 2019)

Sensitivity of Numerical Simulations of a Mesoscale Convective System to Ice Hydrometeors in Bulk Microphysical Parameterization - Zhaoxia Pu; Chao Lin; Xiquan Dong; Steven K. Krueger (Pure and Applied Geophysics, 2019)

Selective, Sensitive and Label-Free Detection of Fe3+ Ion in Tap Water Using Highly Fluorescent Graphene Quantum Dots - Yuanyuan Zhang; Xiangyue Yang; Yunxun Pu; Wei Cheng; Song Lin; Zeyu Shao; Xiaoling Liao (Journal of Fluorescence, 2019)

Constructing a High-Density Genetic Linkage Map for Large Yellow Croaker (Larimichthys crocea) and Mapping Resistance Trait Against Ciliate Parasite Cryptocaryon irritans - Shengnan Kong; Qiaozhen Ke; Lin Chen; Zhixiong Zhou; Fei Pu; Ji Zhao; Huaqiang Bai; Wenzhu Peng; Peng Xu (Marine Biotechnology, 2019)

Applications of Raman spectroscopic techniques for quality and safety evaluation of milk: A review of recent developments - Huirong He; Da-Wen Sun; Hongbin Pu; Lijun Chen; Li Lin (Critical Reviews in Food Science and Nutrition, 2019)

In Vitro Formation of Dickeya zeae MS1 Biofilm - Ning Huang; Xiaoming Pu; Jingxin Zhang; Huifang Shen; Qiyun Yang; Zhongwen Wang; Birun Lin (Current Microbiology, 2019)

Study on Distribution Characteristics of Mining Stress and Elastic Energy Under Hard and Thick Igneous Rocks - Jin-quan Jiang; Quan-sen Wu; Quan-lin Wu; Pu Wang; Chen Zhang; Bin Gong (Geotechnical and Geological Engineering, 2018)

Genome-Scale Association Study of Abnormal Scale Pattern in Yellow River Carp Identified Previously Known Causative Gene in European Mirror Carp - Zhixiong Zhou; Lin Chen; Chuanju Dong; Wenzhu Peng; Shengnan Kong; Jinsheng Sun; Fei Pu; Baohua Chen; Jianxin Feng; Peng Xu (Marine Biotechnology, 2018)

Correlation of IL-31 gene polymorphisms with susceptibility and clinical recurrence of bladder cancer - Qin Li; Tielong Tang; Peng Zhang; Chenlu Liu; Yan Pu; Yan Zhang; Huizi Song; Yanyun Wang; Yaping Song; Min Su; Bin Zhou; Lin Zhang (Familial Cancer, 2018)

A new diaryl 1, 2-diketone from the heartwood of Dalbergia latifolia - Rong-hua Liu; Ding-qing Wang; Pu-zhao Zhang; Feng Shao; Lan-ying Chen; Hui-lian Huang; Shuai Lin (Natural Product Research, 2018)

Association of genetic variations in RTN4 3′-UTR with risk for clear cell renal cell carcinoma - Yan Pu; Peng Chen; Bin Zhou; Peng Zhang; Yanyun Wang; Yaping Song; Lin Zhang (Familial Cancer, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Effects of normoxic and hypoxic exercise regimens on lymphocyte apoptosis induced by oxidative stress in sedentary males - Jong-Shyan Wang; Yi-Ching Chen; Wan-Ling Chen; Chin-Pu Lin (European Journal of Applied Physiology, 2017)

Numerical simulations of an advection fog event over Shanghai Pudong International Airport with the WRF model - Caiyan Lin; Zhongfeng Zhang; Zhaoxia Pu; Fengyun Wang (Journal of Meteorological Research, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Isolation and purification of antialgal compounds from the red alga Gracilaria lemaneiformis for activity against common harmful red tide microalgae - Ying-ying Sun; Kun Meng; Zhen-xia Su; Gan-lin Guo; Yin-fang Pu; Chang-hai Wang (Environmental Science and Pollution Research, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

Daytime warming lowers community temporal stability by reducing the abundance of dominant, stable species - Zhongling Yang; Qian Zhang; Fanglong Su; Chunhui Zhang; Zhichao Pu; Jianyang Xia; Shiqiang Wan; Lin Jiang (Global Change Biology, 2017)
Daytime warming and nighttime warming have the potential to influence plant community structure and ecosystem functions. However, their impacts on ecological stability remain largely unexplored. We conducted an eight‐year field experiment to compare the effects of daytime and nighttime warming on the temporal stability of a temperate steppe in northern China. Our results showed that the cover and stability of dominant species, stability of subordinate species, and compensatory dynamics among species strongly influenced community‐level stability. However, daytime, but not nighttime, warming significantly reduced community temporal stability mainly through the reduction in the abundance of dominant, stable species. These findings demonstrate the differential effects of daytime and nighttime warming on community stability and emphasize the importance of understanding the changes of dominant species for accurately predicting community dynamics under climate warming.

High-intensity Interval training enhances mobilization/functionality of endothelial progenitor cells and depressed shedding of vascular endothelial cells undergoing hypoxia - Hsing-Hua Tsai; Chin-Pu Lin; Yi-Hui Lin; Chih-Chin Hsu; Jong-Shyan Wang (European Journal of Applied Physiology, 2016)

Convergence and divergence in a long‐term old‐field succession: the importance of spatial scale and species abundance - Shao‐peng Li; Marc W. Cadotte; Scott J. Meiners; Zhichao Pu; Tadashi Fukami; Lin Jiang (Ecology Letters, 2016)
Whether plant communities in a given region converge towards a particular stable state during succession has long been debated, but rarely tested at a sufficiently long time scale. By analysing a 50‐year continuous study of post‐agricultural secondary succession in New Jersey, USA , we show that the extent of community convergence varies with the spatial scale and species abundance classes. At the larger field scale, abundance‐based dissimilarities among communities decreased over time, indicating convergence of dominant species, whereas incidence‐based dissimilarities showed little temporal tend, indicating no sign of convergence. In contrast, plots within each field diverged in both species composition and abundance. Abundance‐based successional rates decreased over time, whereas rare species and herbaceous plants showed little change in temporal turnover rates. Initial abandonment conditions only influenced community structure early in succession. Overall, our findings provide strong evidence for scale and abundance dependence of stochastic and deterministic processes over old‐field succession.

Polymorphisms of human 8-oxoguanine DNA glycosylase 1 and 8-hydroxydeoxyguanosine increase susceptibility to arsenic methylation capacity-related urothelial carcinoma - Chao-Yuan Huang; Yeong-Shiau Pu; Horng-Sheng Shiue; Wei-Jen Chen; Ying-Chin Lin; Yu-Mei Hsueh (Archives of Toxicology, 2016)

Deep sequencing of banana bract mosaic virus from flowering ginger (Alpinia purpurata) and development of an immunocapture RT-LAMP detection assay - Jingxin Zhang; Wayne B. Borth; Birun Lin; Kishore K. Dey; Michael J. Melzer; Huifang Shen; Xiaoming Pu; Dayuan Sun; John S. Hu (Archives of Virology, 2016)

Using high spatial resolution satellite imagery for mapping powdery mildew at a regional scale - Lin Yuan; Ruiliang Pu; Jingcheng Zhang; Jihua Wang; Hao Yang (Precision Agriculture, 2016)

Molecular characterization of melanin-concentrating hormone (MCH) in Schizothorax prenanti: cloning, tissue distribution and role in food intake regulation - Tao Wang; Dengyue Yuan; Chaowei Zhou; Fangjun Lin; Rongbin Wei; Hu Chen; Hongwei Wu; Zhiming Xin; Ju Liu; Yundi Gao; Defang Chen; Shiyong Yang; et al. (Fish Physiology and Biochemistry, 2016)

Comparison of vitrified outcomes between human early blastocysts and expanded blastocysts - Wen-yan Song; Xue-gai Wang; Hai-xia Jin; Gui-dong Yao; Xiang-yang Zhang; Sen-lin Shi; Hong-yi Yang; Zhao-feng Peng; Ying-pu Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

Mechanical Behavior of Brittle Rock-Like Specimens with Pre-existing Fissures Under Uniaxial Loading: Experimental Studies and Particle Mechanics Approach - Ri-hong Cao; Ping Cao; Hang Lin; Cheng-zhi Pu; Ke Ou (Rock Mechanics and Rock Engineering, 2016)

Two new alkaloids from Melodinus hemsleyanus Diels - Pu-Zhao Zhang; Ya-Mei Zhang; Jian Gu; Guo-Lin Zhang (Natural Product Research, 2016)

Isolation, purification, and identification of antialgal substances in green alga Ulva prolifera for antialgal activity against the common harmful red tide microalgae - Ying-ying Sun; Hui Wang; Gan-lin Guo; Yin-fang Pu; Bin-lun Yan; Chang-hai Wang (Environmental Science and Pollution Research, 2016)

A review of soil cadmium contamination in China including a health risk assessment - Lin Wang; Xiangfen Cui; Hongguang Cheng; Fei Chen; Jiantong Wang; Xinyi Zhao; Chunye Lin; Xiao Pu (Environmental Science and Pollution Research, 2015)

Green alga Ulva pertusa—a new source of bioactive compounds with antialgal activity - Sun Ying-ying; Wang Hui; Guo Gan-lin; Pu Yin-fang; Yan Bin-lun; Wang Chang-hai (Environmental Science and Pollution Research, 2015)

Complete genome sequence of a new recombinant echovirus 25 strain isolated from a neonatal patient with hand, foot, and mouth disease complicated by encephalitis in Beijing, China - Hongjie Li; Yixing Meng; Lin Pang; Jinqiu Liang; Hongping Lu; Qi Wang; Pu Liang; Jinfeng Cao; Shun-ai Liu; Jun Cheng (Virus Genes, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

EGFR mediates docetaxel resistance in human castration-resistant prostate cancer through the Akt-dependent expression of ABCB1 (MDR1) - Tzyh-Chyuan Hour; Shiu-Dong Chung; Wang-Yi Kang; Ying-Chu Lin; Shu-Ju Chuang; A-Mei Huang; Wen-Jeng Wu; Shu-Pin Huang; Chao-Yuan Huang; Yeong-Shiau Pu (Archives of Toxicology, 2015)

Temperature‐sensitive fitness cost of insecticide resistance in C hinese populations of the diamondback moth P lutella xylostella - Lin Jie Zhang; Yu Pu Jing; Xiao Hui Li; Chang Wei Li; Denis Bourguet; Gang Wu (Molecular Ecology, 2015)
Alleles conferring a higher adaptive value in one environment may have a detrimental impact on fitness in another environment. Alleles conferring resistance to pesticides and drugs provide textbook examples of this trade‐off as, in addition to conferring resistance to these molecules, they frequently decrease fitness in pesticide/drug‐free environments. We show here that resistance to chlorpyrifos, an organophosphate ( OP ), in Chinese populations of the diamondback moth, Plutella xylostella , is conferred by two mutations of ace1 – the gene encoding the acetylcholinesterase enzyme targeted by OP s – affecting the amino acid sequence of the corresponding protein. These mutations were always linked, consistent with the segregation of a single resistance allele, ace1R , carrying both mutations, in the populations studied. We monitored the frequency of ace1R (by genotyping more than 20 000 adults) and the level of resistance (through bioassays on more than 50 000 individuals) over several generations. We found that the ace1R resistance allele was costly in the absence of insecticide and that this cost was likely recessive. This fitness costs involved a decrease in fecundity: females from resistant strains laid 20% fewer eggs, on average, than females from susceptible strains. Finally, we found that the fitness costs associated with the ace1R allele were greater at high temperatures. At least two life history traits were involved: longevity and fecundity. The relative longevity of resistant individuals was affected only at high temperatures and the relative fecundity of resistant females – which was already affected at temperatures optimal for development – decreased further at high temperatures. The implications of these findings for resistance management are discussed.

Challenges and adaptations of farming to climate change in the North China Plain - Hai-Lin Zhang; Xin Zhao; Xiao-Gang Yin; Sheng-Li Liu; Jian-Fu Xue; Meng Wang; Chao Pu; Rattan Lal; Fu Chen (Climatic Change, 2015)

Responses of soil carbon and nitrogen to successive land use conversion in seasonally frozen zones - Xiao Pu; Hongguang Cheng; Mats Tysklind; Shengtian Yang; Chunye Lin; Lu Lu; Jing Xie (Plant and Soil, 2015)

Genetic association study between INSULIN pathway related genes and high myopia in a Han Chinese population - Xiaoqi Liu; Pu Wang; Chao Qu; Hong Zheng; Bo Gong; Shi Ma; He Lin; Jing Cheng; Zhenglin Yang; Fang Lu; Yi Shi (Molecular Biology Reports, 2015)

A polymorphism at miRNA-122-binding site in the IL-1α 3′UTR is associated with risk of epithelial ovarian cancer - Zhu Zhang; Bin Zhou; Qianqian Gao; Yuke Wu; Kui Zhang; Yan Pu; Yaping Song; Lin Zhang; Mingrong Xi (Familial Cancer, 2014)

QTLs for uppermost internode and spike length in two wheat RIL populations and their affect upon plant height at an individual QTL level - Ma Yu; Shuang-Lin Mao; Guo-Yue Chen; Zhi-En Pu; Yu-Ming Wei; You-Liang Zheng (Euphytica, 2014)

An adaptive noise attenuation method for edge and amplitude preservation - Han-Peng Cai; Zhen-Hua He; Ya-Lin Li; Guang-Ming He; Wen Zou; Dong-Jun Zhang; Pu Liu (Applied Geophysics, 2014)

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Commonly Used Excipients Modulate UDP-Glucuronosyltransferase 2B7 Activity to Improve Nalbuphine Oral Bioavailability in Humans - Hong-Jaan Wang; Cheng-Huei Hsiong; Shung-Tai Ho; Min-Jen Lin; Tung-Yuan Shih; Pei-Wei Huang; Oliver Yoa-Pu Hu (Pharmaceutical Research, 2014)

Transcript suppression of TaGW2 increased grain width and weight in bread wheat - Yantao Hong; Longfei Chen; Li-pu Du; Zhenqi Su; Jinfen Wang; Xingguo Ye; Lin Qi; Zengyan Zhang (Functional & Integrative Genomics, 2014)

The roles of autophagy in development and stress responses in Arabidopsis thaliana - Xin Lv; Xiaojun Pu; Gongwei Qin; Tong Zhu; Honghui Lin (Apoptosis, 2014)

Variability of atlantic meridional overturning circulation in FGOALS-g2 - Wenyu Huang; Bin Wang; Lijuan Li; Li Dong; Pengfei Lin; Yongqiang Yu; Tianjun Zhou; Li Liu; Shiming Xu; Kun Xia; Ye Pu; Lu Wang; et al. (Advances in Atmospheric Sciences, 2014)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

Preliminary evaluations of FGOALS-g2 for decadal predictions - Bin Wang; Mimi Liu; Yongqiang Yu; Lijuan Li; Pengfei Lin; Li Dong; Li Liu; Jiping Liu; Wenyu Huang; Shiming Xu; Si Shen; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

The flexible global ocean-atmosphere-land system model, Grid-point Version 2: FGOALS-g2 - Lijuan Li; Pengfei Lin; Yongqiang Yu; Bin Wang; Tianjun Zhou; Li Liu; Jiping Liu; Qing Bao; Shiming Xu; Wenyu Huang; Kun Xia; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Erratum to: Comparison of FÖrster-Resonance-Energy-Transfer Acceptors for Tryptophan and Tyrosine Residues in Native Proteins as Donors - Yi zhang; Xiaolan Yang; Lin Liu; Xuexia Huang; Jun Pu; Gaobo Long; Ling Zhang; Dong Liu; Bangtian Xu; Juan Liao; Fei Liao (Journal of Fluorescence, 2013)

Comparison of FÖrster-Resonance-Energy-Transfer Acceptors for Tryptophan and Tyrosine Residues in Native Proteins as Donors - Yi zhang; Xiaolan Yang; Lin Liu; Zuexia Huang; Jun Pu; Gaobo Long; Ling Zhang; Dong Liu; Bangtian Xu; Juan Liao; Fei Liao (Journal of Fluorescence, 2013)

Equal modulation of endothelial cell function by four distinct tissue-specific mesenchymal stem cells - Ruei-Zeng Lin; Rafael Moreno-Luna; Bin Zhou; William T. Pu; Juan M. Melero-Martin (Angiogenesis, 2012)

Screening for significant atherosclerotic renal artery stenosis with a regression model in patients undergoing transradial coronary angiography/intervention - Li-jin Pu; Ying Shen; Rui-yan Zhang; Qi Zhang; Lin Lu; Feng-hua Ding; Jian Hu; Zheng-kun Yang; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2012)

Identification of a major QTL for silique length and seed weight in oilseed rape (Brassica napus L.) - Pu Yang; Chang Shu; Lin Chen; Jinsong Xu; Jiangsheng Wu; Kede Liu (Theoretical and Applied Genetics, 2012)

Species phylogenetic relatedness, priority effects, and ecosystem functioning - Jiaqi Tan; Zhichao Pu; Wade A. Ryberg; Lin Jiang (Ecology, 2012)
Species immigration history can structure ecological communities through priority effects, which are often mediated by competition. As competition tends to be stronger between species with more similar niches, we hypothesize that species phylogenetic relatedness, under niche conservatism, may be a reasonable surrogate of niche similarity between species, and thus influence the strength of priority effects. We tested this hypothesis using a laboratory microcosm experiment in which we established bacterial species pools with different levels of phylogenetic relatedness and manipulated the immigration history of species from each pool into microcosms. Our results showed that strong priority effects, and hence multiple community states, only emerged for the species pool with the greatest phylogenetic relatedness. Community assembly also resulted in a significant positive relationship between bacterial phylogenetic diversity and ecosystem functions. Interestingly, these results emerged despite a lack of phylogenetic conservatism for most of the bacterial functional traits considered. Our results highlight the utility of phylogenetic information for understanding the structure and functioning of ecological communities, even when phylogenetically conserved functional traits are not identified or measured.

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Inhibition of CYP3A4 and CYP2C9 by podophyllotoxin: Implication for clinical drug–drug interactions - Jin-Hui Song; Dong-Xue Sun; Bin Chen; Dai-Hong Ji; Jie Pu; Jie Xu; Feng-De Tian; Lin Guo (Journal of Biosciences, 2011)

High-precision frequency attenuation analysis and its application - Xiao-Jun Xiong; Xi-Lei He; Yong Pu; Zhen-Hua He; Kai Lin (Applied Geophysics, 2011)

Effect of blue light on indoor seedling culture of Saccharina japonica (Phaeophyta) - Wen-Jun Wang; Xiu-Tao Sun; Guang-Ce Wang; Pu Xu; Xiang-Yu Wang; Zhe-Long Lin; Fei-Jiu Wang (Journal of Applied Phycology, 2010)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Salicylic acid activates artemisinin biosynthesis in Artemisia annua L. - Gao-Bin Pu; Dong-Ming Ma; Jian-Lin Chen; Lan-Qing Ma; Hong Wang; Guo-Feng Li; He-Chun Ye; Ben-Ye Liu (Plant Cell Reports, 2009)

The occurrence of the feline “Candidatus Mycoplasma haemominutum” in dog in China confirmed by sequence-based analysis of ribosomal DNA - Q. J. Zhuang; H. J. Zhang; R. Q. Lin; M. F. Sun; X. J. Liang; X. W. Qin; W. J. Pu; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Genetic analysis of H3 subtype influenza viruses isolated from domestic ducks in northern China during 2004–2005 - Juan Pu; Qin-Fang Liu; Ying-Ju Xia; Yu-Lei Fan; Earl G. Brown; Fu-Lin Tian; Jin-Hua Liu (Virus Genes, 2009)

Molecular cloning of Brassica napus TRANSPARENT TESTA 2 gene family encoding potential MYB regulatory proteins of proanthocyanidin biosynthesis - Yun-Liang Wei; Jia-Na Li; Jun Lu; Zhang-Lin Tang; Dong-Chun Pu; You-Rong Chai (Molecular Biology Reports, 2007)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Spatial correlation analysis of crop yield in the middle and west of Jilin Province - Lin-yi Li; Zhao-li Liu; Chun-lin Li; En-pu Wan (Chinese Geographical Science, 2002)

Study on methods of land use dynamic monitoring at county level - Lin-yi Li; Fang Huang; Zhao-li Liu; En-pu Wan (Chinese Geographical Science, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Stimulation of thymidine kinase activity in baculovirus infected cells is not due to a virus-coded enzyme - X. Wang; W. Xie; Q. Long; D. He; G. Lin; Y. Pang; Z. Pu (Archives of Virology, 1992)